Cardiovascular consequences of vaping. (31st May 2022) - Echeagaray, Oscar; Savko, Clarissa; Gallo, Andrea; Sussman, Mark
Abstract : Purpose of review: Vaping activity continues to increase worldwide. Promoted as a 'healthier' alternative to traditional smoking, emerging evidence indicates 'healthier' should not be confused with 'harmless'. Direct inhalation exposure of the respiratory tract in experimental research demonstrates pulmonary consequences of vaping. However, cardiovascular consequences of vaping are poorly characterized and are a priority area of research to reveal vaping-induced pathogenesis. Recent findings: Alterations in cardiovascular homeostasis, inflammation, and molecular changes following vaping exposure demonstrate vaping-related health concerns. Summary: This review summarizes cardiovascular consequences of vaping from cumulative research findings. Strategic application of emerging technologies to understand the impact of vaping upon the cardiovascular system will be essential for defining the true risks of vaping-associated injury.